Editorial
Presentación de la revista y su relación con el ELEA (Encuentro Latinoamericano de Estudiantes de Arquitectura).
Keywords: ELEA; ENCUENTROS; ARQUITECTURA; ESTUDIANTES; MONTEVIDEO; URUGUAY; REVISTAS